Fostering university-public administration links through local case studies in executive education - Conceição, M. V. da.; Beja, M.; Mamede, R. P. (Teaching Public Administration, 2024)
The gap between public managers and academics has long been a topic of discussion in the field of public affairs. This article presents a successful strategy to bridge this gap: the creation and use of local case studies in executive education for Portuguese public managers. We found that the creation process, which included interviews with practitioners, allowed them to reflect on their work from the framework of academic theories. As for the use of cases in the classroom, the local aspect of the case studies - set in Portuguese institutions, and shaped by the local values, mores, and norms - fostered the appropriation of the subject matter and enhanced the sharing of experiences and ideas, combining academic theory with tacit knowledge from the field. We discuss examples of the observed benefits, as well as the challenges and possibilities of replicating the strategy in other contexts.